Economic Exchange and Social Interaction in Southeast Asia Perspectives from Prehistory, History, and Ethnography - Hutterer, Karl L. (Michigan Papers On South And Southeast Asia, 2020)
Economic behavior is governed by two major sets of boundary conditions: environmental and technological factors on the one hand, and conditions of social organization on the other hand. Indeed, social scientists are often particularly interested in the framework of exchange relationships: exchange of goods, services, personnel, and information. Economic exchanges lend concrete manifestations to social relations that themselves may transcend the economic realm and that otherwise are often difficult to trace. Yet in social science research in Southeast Asia, the area of economic studies has lagged behind, despite the great study potential represented by the tremendous diversity of its physical and human environment. Economic Exchange and Social Interaction in Southeast Asia attempts to take advantage of that opportunity. As a number of the contributions to this volume show, many if not most of the systems organized on very different levels of integration interact with each other. Taken as a whole, they provide evidence of the incredible diversity of economic and social systems that may be investigated in Southeast Asia.